Utilization of bar and izakaya-pub establishments among middle-aged and elderly Japanese men to mitigate stress - Ohnishi Mayumi; Nakao Rieko; Kawasaki Ryokko; Nitta Akiko; Hamada Yukari; Nakane Hideyuki (BMC, 2012)
Abstract Japanese suicide rate is one of the highest among industrialized nations, especially following the economic crisis of the 1990s, with more than 30000 suicides every year since 1998. Previous studies have pointed out to relationships between overwork and/or job stress, and death and other health risks, and suggested several possible avenues for releasing stress and emotional burden, including suicidal ideation, through talking with intimate friends, family, and specialists, such as counselors and physicians. The present study was performed to explore the potential role of owners and managers of bars and izakaya-pub establishments in mitigating stress of middle-aged and elderly Japanese men by having informal conversations with them. A self-administered questionnaire was posted to all bars and izakaya-pubs registered in Ohmura-city, Nagasaki prefecture, in December 2009. Among 260 bars and izakaya-pubs, a total of 103 owners and managers completed the questionnaire. More than half of the respondents experienced engaging in conversations with their customers regarding customers' various personal and private issues. The most frequently talked about problem was that regarding work (56.3%). Regardless of sex and age of the respondents, those with longer working experience in bar and izakaya-pub establishments were more likely to have had customers confiding in them financial problems including debts/loans (adjusted odds ratio: 5.48, p = 0.033). Owners and managers of bars and izakaya-pubs may be in a position to act as "listeners", to whom middle-aged and elderly men can talk about their personal problems casually and without having to worry about conflict of interests, and direct those in need to professional counseling.